Bureaucracy and public labor market in Colombia. ¿Convergence or divergence? - Rodríguez Hernández, Jairo Enrique (Revista del CLAD Reforma y Democracia, 2025)
The public labor market has lived some changes with opposing trends. On one side, there is a greater presence of selection based on meritocracy; on the other hand, there is increasing flexibility of the labor market, through the hiring of personnel through service provision and management support contracts, as well as the development of the figure of temporary jobs. These trends show the contradiction between the strengthening and weakening of bureaucracy, especially from the year 2000 onwards in the Colombian case. The labor formalization policy, a key proposal by the government of Gustavo Petro, is at the center of this debate, because it drives to a increasing process of bureaucratization in a landscape, where social, economic, technological and political changes are shaping flexible forms of employment relationships, where stable and lifelong work may be doomed to disappear.
Keywords: public sector; administrative career system; staff recruitment; bureaucratization; labor flexibility